ESG Controversies and Bank Risk-taking: Islamic vs Conventional Banks - Kemala Putri Ayunda; Yunice Karina Tumewang (Muslim Business and Economics Review, 2025)
Environmental, social, and governance (ESG) controversies have gained increasing attention due to their potential financial and reputational risks, particularly within the banking sector. As regulatory pressures and stakeholder expectations escalate, understanding the impact of ESG controversies on banks' risk-taking behavior is critical for financial stability and sustainable banking practices. This study investigates the relationship between ESG controversies and bank risk-taking, comparing Islamic and conventional banks within the Organisation of Islamic Cooperation (OIC) countries. Using a panel dataset covering 35 Islamic banks and 68 conventional banks across 11 OIC countries between 2013 and 2022, we apply a fixed-effects regression model to assess the influence of ESG controversy exposure on bank risk. The results demonstrate that Islamic banks are significantly less exposed to ESG controversies than conventional banks, reflecting the normative ethical underpinnings of Islamic finance. However, Islamic banks exhibit higher risk levels compared to their conventional counterparts. The regression analysis also reveals that, in both the full sample and the conventional bank sub-sample, fewer ESG controversies are significantly associated with lower risk-taking, thereby enhancing bank stability. However, this effect is absent in Islamic banks. These results highlight the critical role of institutional, cultural, and regulatory contexts in shaping how ESG controversies influence bank behavior. While ESG controversies may act as effective risk control signals in conventional banking systems, their impact appears attenuated in Islamic banks, where ethical principles are already embedded in financial practices.